Cervical Thymic Cyst with parathyroid tissue - a diagnostic conundrum - Deepika Gupta; Darwin Kaushal; Deepak Vedant; Rashim Sharma; Vikarn Vishwajeet; Poonam Abhay Elhence (University of São Paulo, 2022)
Cervical thymic cysts are relatively rare benign cystic lesions that tend to be diagnosed clinically as branchial cysts, which usually present as painless, enlarging neck masses. They can occur anywhere along the normal path of descent of thymic primordia from the angle of the mandible to the sternal notch, with mediastinal extension observed in approximately 50% of cases. They are usually seen in the first decade of life on the left side with a male predominance. Here we report a case of a 15-year-old boy who presented to the hospital with left-sided neck swelling for about 2 months. The neck's contrast-enhanced computed tomography (CECT) revealed a large, well-defined cystic swelling in the left neck region, showing peripheral enhancement, seen from the submandibular region to the superior mediastinum extending into the retrosternal region. Direct fine needle aspiration (FNA) was done, which showed a benign lesion with inflammatory and cystic characteristics, leading to the possibility of a branchial cyst. The cyst was completely excised surgically. Histopathology showed a thymic cyst with parathyroid tissue. The presence of thymic tissue with Hassall's corpuscles is essential for the diagnosis. Knowledge of the clinical presentation, cyto-histological findings, and differential diagnosis of cystic cervical lesions in the pediatric population is important to diagnose this rare entity. Hence, though uncommon, when one comes across a cystic cervical region mass in children, a diagnosis of cervical thymic cyst should be kept in mind. Nonetheless, a definitive diagnosis depends on imaging findings as well as intraoperative findings and histopathological examination.